DAMPAK CORPORATE GOVERNANCE TERHADAP COST OF CAPITAL DI INDUSTRI MANUFAKTUR DI INDONESIA - Setiawan, Abdurrahman (Lembaga Penerbitan Unversitas Esa Unggul, 2020)
This research was conducted to examine the effect of corporate governance index, block ownership and director ownership of the company. The sample used in this study was manufacturing companies listed on the Indonesia Stock Exchange for the period 2014 - 2018. Sampling was carried out by purposive sampling to obtain 26 manufacturing companies to be examined. The dependent variable is cost of capital while the corporate governance index, block ownership and director ownership are independent variables. Sales growth, firm size, leverage, corruption index, inflation and gross domestic product as control variables. The results of this study indicate that firm size and inflation have a positive and significant influence on the cost of capital. Whereas corporate governance index, block ownership, director ownership, sales growth, leverage, corruption index and gross domestic product have no significant effect on the cost of capital. Implications for financial managers pay attention to factors that can affect the cost of capital in manufacturing companies and for investors choosing investments that can increase profits and prosperity in the future. Suggestions for further research are expected to add to the financial statement period and to add independent variables, namely earnings management and information asymmetry. In the novelty of this study, the research analysis method only until the t test (Individual) didn’t use robustness check as previous studies because this study didn’t have outlier data.